Sintesis Biodiesel Dari Minyak Biji Nyamplung (Calophyllum Inophyllum) Menggunakan Katalis Geopolimer Dari Abu Sekam Padi Dan Kaolin - M. Wahyu Nugraha; Edy Saputra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is an alternative diesel fuel produced from vegetable oil triglycerides transesterification reaction. Besides being derived from renewable sources, biodiesel generate emissions better than diesel. Utilization of vegetable oils such as potential as Calophyllum inophyllum seed oil as raw material biodiesel because it is non-edible. It is necessary to develop catalyst technology in order to get the production process becomes more economical, applicable, and environmentally friendly, one of the catalysts is rice husk ash (RHA) geopolymer. The geopolymer synthesized by reacting sodium silicate, metakaolin, NaOH, and water. Characterized geopolymer produced include alkalinity, surface morphology, elemental composition, and surface area. The variation of process variables conducted to assess the effect on the yield of biodiesel. Independent variable weight of oil 50 grams, mole ratio methanol:oil 9: 1, reaction time 120 minutes, and temperature of 65 °C, with the dependent variables %w/w catalyst 0.79%-2.2% and stirring rate 117-682 rpm. The result of physical characterization density 866 kg /m3, viscosity 4.13 mm2/s, acid number of 0.42 mg-KOH/g biodiesel and flash point 140 °C meet the SNI standards (SNI 7182: 2015).Keywords: Biodiesel, Calophyllum inophyllum Oil, Catalyst, Geopolymer, Rice Husk Ash